CCCIIs-based sinusoidal quadrature oscillators with non-interactive control of condition and frequency - Summart, Saksit; Thongsopa, Chanchai; Jaikla, Winai (My University, 2014)
The paper presents two current-mode quadrature oscillators with non-interactive two current controls for both of the condition of oscillation (CO) and the frequency of oscillation (FO) using current controlled current conveyors (CCCIIs). The proposed oscillators can provide two sinusoidal output currents with 90 degrees phase difference. It also provides high output impedances that make the circuit can directly drive load without additional current buffer. The condition of oscillation and frequency of oscillation can be controlled by adjusting the bias currents of the CCCIIs. The proposed circuits use only grounded capacitors without any external resistor which is very appropriate for further development into an integrated circuit. The results of PSPICE simulation program are corresponding to the theoretical analysis. Copyright © 2012 The Council of Scientific and Industrial Research, New Delhi.
Keywords: CCCII; Current-mode; High output impedance; Non-interactive control; Quadrature oscillator